Diseño y simulación de un prototipo de silla salvaescaleras de bajo costo para viviendas de personas con movilidad reducida (2021)
In Colombia, approximately 12% of the population has a disability condition. In the department of Huila, an average of 72 thousand diagnosed people are registered. These people have limited mobility especially in homes because they do not adjust to their physical needs, but above all because there are no low-cost stairlifts in the current market. The purpose of this work is to design and simulate a low-cost stairlift prototype, aimed at Colombians and mainly “opitas” who are in conditions of disability. The methodology used for the research included the study in the literature of the main operating characteristics, components, and existing contributions in thistype of technology. Next, the design process was developed using the Inventor and Fusion 360 software. Finally, different simulations were carried out, among which are: load analysis, Von Mises stress, safety analysis and displacement analysis, obtaining a stairlift that it supports the maximum loads and voltages established, as well as a simple, safe, resistant, and low-cost product